Correlation between Hypertension and the Severity of Diabetic Retinopathy in Diabetes Mellitus Patients at Waled Regional General Hospital: A Cross-Sectional Study - Trinanda, Syifa Khaerunisa; Sisprihattono, Boyke; Astuti, Widi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Diabetes mellitus is a metabolic disorder characterized by elevated blood sugar levels and resulting from deviations in either insulin secretion, insulin action, or both. Prolonged hyperglycemia can lead to various complications, including diabetic retinopathy. The main risk factors for developing diabetic retinopathy are uncontrolled diabetes mellitus, hypertension, and dyslipidemia. Aims: To determine the correlation between hypertension and the severity of diabetic retinopathy in diabetes mellitus patients at Waled Regional General Hospital, Cirebon, from 2020 to 2023. Methods: This study used an analytical observational method with a cross-sectional design. We collected data from the medical records of patients with diabetic retinopathy at Waled Regional General Hospital from 2020 to 2023. This study employed total sampling as its sampling technique. We performed univariate analysis to determine the frequency distribution of the samples and bivariate analysis using the Spearman correlation test. Results: Out of 50 diabetic retinopathy patients, the majority suffered from proliferative diabetic retinopathy (PDR), with 22 (44%) patients. The most common blood pressure level among the patients was grade 2 hypertension, with 19 (38%) patients. The bivariate analysis in this study showed a P-value of 0.091 and an r-value of 0.242. Conclusion: There is no significant correlation between hypertension and the severity of diabetic retinopathy in diabetes mellitus patients at Waled Regional General Hospital from 2020 to 2023, with a positive correlation direction (p-value: 0.091 and r-value: 0.242). Received: 25 September 2024 | Reviewed: 16 October 2024 | Revised: 30 November 2024 | Accepted: 12 December 2024.